Open Field Layout Problem Using Hybrid Approaches: A Systematic Review - Montreano, Donny; Daihani, Dadan Umar; Septiani, Winnie; Suhardini, Didien (Spektrum Industri, 2025)
The Open Field Layout Problem (OFLP) is a free-configuration layout problem characterized by the absence of floor constraints and an unlimited number of potential solutions. This systematic literature review analyzed over 3,000 Scopus-indexed articles using the keyword "facility layout problem" and related terms, identifying 154 studies that applied hybrid approaches. Terms such as two-stage, multi-stage, or similar variations were classified accordingly. The review revealed that OFLP is not a monolithic concept but comprises five principal types: (1) layouts without aisles or floor boundaries, (2) tightly packed layouts with minimal spacing, (3) layouts with aisles and large residual space, (4) layouts with aisles and floor boundaries, and (5) layouts with aisles but no floor boundaries. The first type is most commonly addressed, while the fifth remains underexplored. This classification highlights a critical research gap and points to opportunities for advancing from low- to high-level hybrid strategies